The effect of psychological contract, organizational justice and organizational support on psychological contract breach: the mediating effect of trust - Faruk, Shakur (2019)
The purpose of this study is to examine the effect of psychological contract, organizational justice and organizational support on psychological employment contract breach in Nigeria public universities, with the mediating effect of trust. Stratified random sampling technique was used in data collection, with a sample size of 513.The retrieved data was analysed using statistical package of social science SPSS (version 24), and thus, executed factor analysis and multiple regression analysis in examining the significant effect between the study variables. Also, this study used both descriptive and inferential statistics in analysing data. This study revealed that, after factor analysis, the dimensions of independents variables namely; transactional contract, distributive justice and perceived organizational support have a significant effect on the dimensions of dependent variable which is unfulfilled promises and employees frustration respectively. The multiple regression results found that trust partially mediated the effect between distributive justice and employees’ frustration, trust also shows a partial mediation between perceived organizational support and employees’ frustration. This study contributes to the literature on how trust serves as a mediating variable between psychological contract, organizational justice, perceived organizational support and psychological employment contract breach in Nigeria public universities. Lastly, study implications, limitations, conclusion as well as suggestion for future research were discussed.